The effect of transient receptor potential vanilloid 4 (TRPV4) ligands on lipocalin2 adipocytes lipid chaperone protein signalling - Mohd Radzuan, Hazulin; Wan Omar, Wan Fatein Nabeila; Bennett, Andrew J.; Cole, Mark (2021)
Introduction: The ambiguous role of lipocalin2 (LCN2), one of the adipocytes lipid chaperone proteins (LCPs) is intriguing. It is being described as causing insulin resistance or sensitization in different model systems. It is believed that its regulation is affected by the action of exogenous ligands towards adipocytes receptors. Since calcium plays an important role in adipogenesis, transient receptor potential vanilloid 4 (TRPV4), a calcium permeable non-selective cation channel may play a role in regulating adipocytes LCPs metabolism. Objective: To determine the effect of TRPV4 ligands towards adipocytes LCN2 signalling in different glucose concentration media. Methods: Primary adipocyte culture from male Wistar rats were maintained in normal glucose (NG = 6 mM/L) and high glucose (HG = 17.5 mM/L) concentration media. They were differentiated for 10 days and treated with 100nM GSK101 (TRPV4 agonist) and 500nM HC067 (TRPV4 antagonist). After 24h incubation, conditioned media was collected for secreted protein extraction, while RNA and cell lysate were extracted from adherent adipocytes for gene and protein expression analysis. These samples were analysed using RT-PCR and western blotting, and interpreted by GraphPad Prism (GraphPad Software, San Diego) and ImageJ (National Institutes of Health, USA). Results: GSK101 diminished LCN2 expression; while HC076 did not affect LCN2 gene level in HG, but raised the expression significantly in NG (p < 0.01). Similarly, GSK101 reduced LCN2 protein expression and secretion in HG, unlike HC067 that had no profound effect. Further evaluation using two-way ANOVA showed significant interaction between the effect of both glucose and TRPV4 treatments (F(2,12) = 17.33, p = 0.0003) towards LCN2 expression. Conclusion: The interplay between HG and GSK101 significantly suppressed LCN2 expression and secretion, but presence of HC067 in NG promoted the expression of LCN2 gene. Since calcium has an inhibitory effect to adipogenesis, LCN2 can be a potential biomarker in metabolic diseases.